Paper Makers in Canada: A History of the Paper Makers Union in Canada - Greening, William E. (International Brotherhood of Paper Makers, 1952)
Contents: Origin of the union -- The struggle for recognition in the province of Quebec -- Recent progress.
Keywords: Canada; International Brotherhood of Paper Makers; International Brotherhood of Paper Makers Canada Histoire; Paper industry; Paper industry Canada; Paper industry workers; Paper industry workers Canada; Papier Industrie Canada